2020
DOI: 10.5380/ce.v25i0.72659
|View full text |Cite
|
Sign up to set email alerts
|

Planejamento Operacional Durante a Pandemia De Covid-19: Comparação Entre Recomendações Da Organização Mundial Da Saúde E O Plano De Contingência Nacional

Abstract: Objetivo: frente à divulgação do guia COVID-19 - Operational Planning Guidelines to Support Country Preparedness and Response, pela Organização Mundial da Saúde, esta comunicação buscou comparar o conteúdo do Plano de Contingência Nacional às orientações da Organização Mundial da Saúde.Desenvolvimento: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov2), causador da COVID-19, apresenta transmissão comunitária sustentada no Brasil desde março de 2020. O país lançou seu Plano de Contingência Nacional par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 5 publications
1
4
0
16
Order By: Relevance
“…Although it is difficult to quantify how many contacts people usually have, the estimates presented help to understand the need for physical isolation, since the data present in this study showed a significant correlation for social isolation, compared to the speed of new cases, corroborating with other research which highlighted the need for a minimum reduction of 75% for symptomatic people and 55% for asymptomatic ones, as the contact reduction rate necessary for better control of transmission (13) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although it is difficult to quantify how many contacts people usually have, the estimates presented help to understand the need for physical isolation, since the data present in this study showed a significant correlation for social isolation, compared to the speed of new cases, corroborating with other research which highlighted the need for a minimum reduction of 75% for symptomatic people and 55% for asymptomatic ones, as the contact reduction rate necessary for better control of transmission (13) .…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the exponential increase in the new records observed authenticates the rapid increase in clinical cases of the new disease, conferring the coronavirus as highly transmissible, even though the estimates of the basic reproductive number, reported in the literature, vary widely (13) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Quanto às ações de prevenção e controle direcionadas à redução da disseminação do coronavírus, 50% dos artigos abordaram que as principais ações de prevenção e controle está voltada aos profissionais do setor saúde, como para a população (COSTA et al, ANTUNES et al, 2020;OLIVEIRA et al, 2020;MARQUES et al, 2020;GALLASCH et al, 2020;DE ALBUQUERQUE, 2020;MOREIRA et al, 2020;OLIVEIRA;IQUIAPAZA, 2020;SILVA et al, 2020(b); PORTO, 2016).…”
Section: Medidas De Prevenção E Controleunclassified
“…As manifestações clínicas do COVID-19 representam importantes desafios ao sistema de saúde pública brasileira, considerando uma possível insuficiência de leitos, equipamentos e profissionais para atender a um país de extensa proporção territorial como o Brasil 10 .…”
Section: A Pandemia Covid-19 E As Repercussões Na Atenção à Saúde Do unclassified